A New Insight Into Sudden Cardiac Death in Young People. Issue 32 (August 2015) - Wang, Yueyue; Xia, Lei; Shen, Xiaodong; Han, Guoxin; Feng, Dan; Xiao, Hongju; Zhai, Yongzhi; Chen, Xin; Miao, Yuanyuan; Zhao, Chunhong; Wang, Yingchan; Guo, Mingguang; et al.
<x xml:space="preserve">Abstract</x> Abstract Takotsubo cardiomyopathy (TTC) causes sudden cardiac death and has garnered increased attention worldwide in recent years. However, few studies have clearly classified the risk factors for this disease, including gender, race and morbidity, as well as the physical and mental stressors that can exacerbate the disease, particularly in young patients. To better analyze the characteristics of young TTC patients, we performed a systematic review of reported cases involving young patients. A computer-assisted search was performed using prominent electronic medical information sources to identify literature published between January 1965 and December 2013. Relevant studies containing clinical data of young TTC patients were included. Ninety-six records that included information about 104 cases were ultimately selected for our review. Several of the following results were noted: First, physical stress was more likely to exacerbate TTC than was mental stress in young patients. Second, more female than male TTC patients were noted among both young patients and the general population. Third, ethnicity appears to play no role in the disease, as no significant differences were noted among individuals of different races with respect to clinical characteristics, morbidity or stressors. Fourth, the clinical manifestations of TTC were similar to those of other cardiac diseases, including coronary heart disease. However, TTC may be detected using the combination of echocardiography and ventriculography. Clinicians should consider TTC if young patients present with symptoms similar to those of coronary heart disease so that harmful treatments such as coronary artery stent placement may be avoided. Moreover, the answers to questions regarding the clinical diagnostic criteria, etiology, pathophysiology, and the management of this syndrome in youth remain unclear; therefore, further research is needed.